2016
DOI: 10.1155/2016/3746791
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell-Inner Plexiform Layer, Peripapillary Retinal Nerve Fiber Layer, and Macular Thickness in Eyes with Myopicβ-Zone Parapapillary Atrophy

Abstract: Purpose. To assess the correlations of myopic β-zone parapapillary atrophy (β-PPA) with the optic nerve head (ONH) and retina. Methods. We selected 27 myopic patients who showed prominent β-PPA in one eye and no β-PPA in the other eye. We studied their macula, macular ganglion cell-inner plexiform layer (mGCIPL), peripapillary retinal nerve fiber layer (pRNFL) thickness, and ONH parameters using optical coherence tomography. Results. The average of five out of six sectors and minimum values of mGCIPL thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…In a previous study, a tilted disc was commonly found in myopic eyes, and it was associated with a decreased RNFL thickness, particularly in myopic eyes with beta-zone parapapillary atrophy. 16 That finding was consistent with our DFT analysis.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, a tilted disc was commonly found in myopic eyes, and it was associated with a decreased RNFL thickness, particularly in myopic eyes with beta-zone parapapillary atrophy. 16 That finding was consistent with our DFT analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the previous reports, we found that males have a greater macular thickness after adjusting for DFD and other covariates. It has been reported that eyes with β - PPA tend to have a thinner macular thickness 36 . In line with previous studies 26 , 36 , we found that eyes with β - PPA had a thinner macular thickness and a greater DFD.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that eyes with β - PPA tend to have a thinner macular thickness 36 . In line with previous studies 26 , 36 , we found that eyes with β - PPA had a thinner macular thickness and a greater DFD. In the multivariable analysis, however, the presence of β - PPA was not associated with macular thickness.…”
Section: Discussionmentioning
confidence: 98%
“…AL appears to be significantly associated with both β -PPA [ 23 ] and decreased macular vasculature [ 24 ], and the latter two variables are affected by multiple factors. However, myopic disc changes are not always accompanied by axial elongation, which varies among individuals [ 25 ], suggesting that β -PPA also plays an important role in vasculature changes. In our study, the retinal vasculature parameters were all associated with AL and β -PPA.…”
Section: Discussionmentioning
confidence: 99%